Evaluating visitor experience of digital interpretation and presentation technologies at cultural heritage sites: a case study of the old town, Zuoying - Ying Liu (Built Heritage, 2020)
Abstract Digital technologies are increasingly used in the interpretation and presentation process at cultural heritage sites, shifting the manner of heritage display from previous ways, which tended to be monolithic and static, to a more diversified, experiential, and interactive approach and enabling new connections between heritage and the public. Digital experience is gradually becoming an important component of visitors’ heritage experience. However, little attention has been paid to the influence and effects that these technologies have on the visitor experience, and a corresponding measurement framework for the heritage digital experience is still lacking. To contribute to the design, implementation, and management of digital display systems at cultural heritage sites, this research aims to evaluate visitors’ expectations, acceptance, and experience of digital interpretation and presentation technologies. A mixed methodology, combining questionnaires based on a digital experience evaluation framework and semi-structured interviews, was adopted and used in Old Zuoying City (OZC), a typical heritage site for the application of digital display technologies in Taiwan. Our study indicates that digital display technologies received high acceptance from heritage visitors and had a positive impact on some specific aspects, such as encouraging their exploration of and further learning about the site, helping them better visualize the richness of heritage, and creating new experiences of perceiving, engaging, and communicating with history. In addition, based on the survey findings, a number of recommendations for the current stage of digital display design are presented. The survey results and evaluation framework can be used as a reference for other research on heritage visitors and to improve digital interpretation and presentation design.